A-37 Ocular Motor Impairments in Concussion Professional Football Players. (13th July 2022) - Ree-Fedun, Q; Naidu, D; Mrazik, M; David, C; Hansen, J; Wagner, R; Arends, T
Abstract: Purpose: The purpose of this study was to examine baseline and post-concussion injury characteristics of ocular eye movements using the Sync Think visual eye tracking apparatus in professional football players in the Canadian Football League (CFL). Methods: The visual tracking testing protocol uses an integrated stimulus presentation-eye tracking apparatus (EyeLink CL; SR Research, Ontario, Canada) with which eye movements were recorded at 500 Hz using infrared video-oculography. The standard deviation of radial errors (SDRE) and tangential errors (SDTE) were used to determine poor visual tracking. Participants were (n = 748) rostered players in the Canadian Football League. All participants completed assessments at baseline. Sixteen players completed post-concussion assessments and 98 players completed post-exertional assessments during the 2021 season to evaluate the impact of physical exertion on ocular movement metrics. Results: Participants with diagnosed concussions (n = 16+) demonstrated significantly poorer performance on measures of both gaze stability and smooth pursuit (p < 0.001). The poorer results were correlated with significantly higher subjective ratings of dizziness (p < 0.01) and fogginess (p < 0.001). In contrast, healthy participants who completed the same ocular motor assessments demonstrated no significant differences compared to baseline test performance. Conclusions: Findings suggest that subtle differences in oculomotor functioning arise from sport concussion in professional football players. Further research with larger sample sizes and correlation with other cognitive and physical outcomes is warranted.